Consumption of trastuzumab in the Oncological Mixtures Unit of Edgardo Rebagliati Martins National Hospital, January-December 2009 - Gallegos, Jim W. (2011)
The consumption of trastuzumab in oncological mixtures Unit (UMO) of the Hospital Nacional Edgardo Rebagliati Martins was studied during 2009 through retrospective descriptive analysis of the worksheets from the UMO and using of Hospital Management System (SGH) and analysis of written and dispensed prescriptions. The results show that the cost accounting of chemotherapy schemes was S/.72798,21 for each patient, still the most widely consumed trastuzumab more ixabepilone mixture with an average cost for six cycles S/. 68684, 52. The UMO attended 542 prescriptions and 521 preparations with trastuzumab, which generated an expense of S/. 3798426 and refunds amounted to S/. 704442, this generated a savings of 18,55%.